Public Perception of Visual Quality of Cut Mutia Mosque Park as Public Space in Jakarta - sadana, agus s (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2015)
Cut Mutia Park is a city park which is an integral part and attached to the main courtyard of the mosque cut mutia. This park is a green open space that serves as a public space and generate the aesthetics of the city. There are seven critical elements that need to be studied to determine the public's perception of the park. Knowledgeable public perception of these elements, useful for city authorities in the development of city parks for future. The results of the research showed that of the seven elements studied, only two elements of which will be a positive perception, namely aspects of cleanliness and coolness, while five other aspects got a negative perception. As a result, generally Cut Mutia Parks research object only gets the value perception of -0.24. Details of the value obtained by each of these aspects are: -0.52 for comfortability; +0.13 for cleanliness; -0.003 for freshness; +0.26 for coolness; -0.77 for harmony level; -0.42 for beauty level; and -0.32 for interesting presented. Low perception from respondents indicated that Cut Mutia Park need better design such that it can give added value to the mosque and the environment surrounding. At the end can be said that the city authorities need to further improve attention in structuring of the park, to makes Cut Mutia Park become more comfortable, interesting and favored by the public, and also strengthening the power of the mosque as the central point.